Stability of sulfadiazine sugar-free oral suspensions for the treatment of congenital toxoplasmosis (Brazilian Journal of Pharmaceutical Sciences, 2023)
This study aimed to develop and evaluate the stability of sulfadiazine sugar-free extemporaneous oral suspensions, focusing on treating congenital toxoplasmosis. The excipients were carefully chosen to obtain safe products for the pediatric population. Sulfadiazine suspensions (100 mg/ mL) were prepared from the raw material or tablets, stored in amber glass bottles at 5±3ºC, and evaluated at 0, 14, and 30 days. An ultra-performance liquid chromatographic method was developed and validated to assay the drug. The particle size ranged from 29.3 to 50.6 µm, with some variation over the study; pH values around 7.0 and non-Newtonian behavior were observed without modification in the period. Formulations showed a fast dissolution rate (>80% in 15 minutes) without variation over the study. The drug assay was about 100% of the label claimed throughout the study, demonstrating the chemical stability and the preparations’ dose homogeneity. The microbiological investigation indicated that both preparations met the requirements for the microbial count and absence of pathogens. In conclusion, the developed formulations can be used for 30 days when stored under refrigeration. The oral suspensions produced are easy to prepare and contain safe components, providing an alternative for congenital toxoplasmosis treatment in children.